2021
DOI: 10.1080/1828051x.2020.1801358
|View full text |Cite
|
Sign up to set email alerts
|

Effects of probiotics complex supplementation in low nutrient density diet on growth performance, nutrient digestibility, faecal microbial, and faecal noxious gas emission in growing pigs

Abstract: The objective of the present study was to evaluate the effect of supplementing low nutrient density diet of growing pigs with probiotics complex on growth performance, nutrient digestibility, faecal microbial, and faecal noxious gas emission. A total of 140 crossbred female and castrated male healthy growing pigs [(Yorkshire  Landrace)  Duroc, 54 days of age] with an average initial body weight (BW) of 24.39 ± 2.58 kg were used in a 42-day trial. All pigs were randomly allotted to one of four treatment diets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…than the BSFL12 diet. This result was consistent those of Wang et al [47], who showed that the inclusion of 0.1% multi-probiotics (consisting of B. subtilis, B. licheniformis, and S.…”
Section: Microbial Countsupporting
confidence: 93%
“…than the BSFL12 diet. This result was consistent those of Wang et al [47], who showed that the inclusion of 0.1% multi-probiotics (consisting of B. subtilis, B. licheniformis, and S.…”
Section: Microbial Countsupporting
confidence: 93%
“…This review outlines two applications for reduction of antibiotic use, including for growth promotion and disease prevention. An overview of possible antibiotic alternatives for growth promotion derived from previous studies is presented in Supplementary Table 1 (Cha et al, 2012;Kim et al, 2014;Yoon et al, 2014;Zeng et al, 2014;Devi et al, 2015;Gois et al, 2016;Hossain et al, 2016;Lee et al, 2016;Peng et al, 2016;Sbardella et al, 2016;Tang et al, 2016;Upadhaya et al, 2016;Wan et al, 2016;Lan et al, 2017;Lei et al, 2017;Ma et al, 2017;Pan et al, 2017;Wu et al, 2017;Huang et al, 2018;Lei et al, 2018;Samolińska et al, 2018;Sayan et al, 2018;Seo et al, 2018;Xu et al, 2018;Pei et al, 2019;San Andres et al, 2019;Wang et al, 2019;Duarte et al, 2020;Petry et al, 2020;Ren et al, 2020;Satessa et al, 2020;van der Peet-Schwering et al, 2020;Wei et al, 2020;Zhang et al, 2020;Sun et al, 2021;Wang et al, 2021). These vary considerably from chemical compounds, biologically active substances, and microbially derived products.…”
Section: Alternatives To Antibioticsmentioning
confidence: 99%
“…The antagonistic effect of such probiotics on the pathogenic gut microflora of humans and animals has been known since long ago [6]. However, most research about the effect of dietary administration of probiotic Bacillus strains on growth performance has been conducted in chicken, mouse, and pig [7][8][9][10], and yet only recently it was experimentally shown that certain strains of B. subtilis can provide beneficial effects on the growth of young broiler chickens and have the potential to replace antibiotic growth promoters [11] or improve egg quality [12]. Similar studies on ducks have been fewer [13,14], and we failed to find reports on gut microbiome research using probiotic Bacillus strains for Pekin ducks.…”
Section: Introductionmentioning
confidence: 99%